PENERAPAN IPTEK BIOGAS “MENUJU KONSEP DESA MANDIRI ENERGY-DME” DI DESA RARANG LOMBOK TIMUR - Mara, I Made; Suartika, I Made (Universitas Mataram, 2015)
The implementation of science and communities service project is aimed to minimize destitution by implementing self feeding and energy generating village concept. The specific goal of this project is the utilization of cattle dung to produce a biogas. The method is being used for this project is by illuminating and educating the community to be able to build and operate the cattle dung biogas digester by their own. In addition, the community is completely involved to this project since the early state of this project. By implementing the plastic floating digester, it is hoped that the communities be able to utilize the biogas digester and make their own domestic energy. The result of this program is an unit biogas digester by using cow dung as a feed stock. The plastic floating digester can produce a continue biogas as a fuel for cooking. The enthusiasm of the community in term of using and implementing the digester is quite high. It is expected that the community can build and implement the cattle dung digester to produce biogas as a domestic energy.